Development of 3S-Based Nursing Care Instruments (SDKI, SLKI, SIKI) in Patients with Ventilators - Ambarwati, Diah Retno; Kurniawati, Ninuk Dian; Airlangga, Prananda Surya; Zamroni, Asroful Hulam (Indonesian Journal of Global Health Research, 2024)
Documentation instrument for quality nursing care according to standards. However, there is no instrument for nursing care for patients installing ventilators according to Indonesian nursing standards. This research aims to develop a 3S-based nursing care instrument (SDKI, SLKI, SIKI) for ventilator patients. The research design is Research and Development carried out in 2 stages. The first phase population is 100 nursing care. The first stage was FGD 1, divided into 3 groups, namely 10 executive nurses, 6 nursing management staff, and 1 expert. The second stage population was 5 nurses. The second stage was carried out FGD 2 with participants from 6 levels of nursing management. The sample used in this research was purposive sampling. The design developed is an instrument for documenting nursing care for ventilator patients. The analysis uses the CVI and KR20 tests. Results: Evaluation of nursing care instruments shows that aspects of nursing outcomes, implementation, and evaluation are not by standards. Instrument development consists of 5 main problems that often arise in ventilator patients. The I-CVI result is ≥ 0.78, which is interpreted as valid. The KR result is > 0.6, which means it is reliable. The recommendation from the research results is that the development of nursing care instruments can be applied in treating patients with ventilators. Conclusion: The development of a nursing care instrument was declared to be valid and reliable in categories in terms of functionality, efficiency, and usability, so it is recommended that nurses use it to improve the quality of hospital services.